2019
DOI: 10.1016/s2215-0366(19)30001-x
|View full text |Cite
|
Sign up to set email alerts
|

The psychopathology of NMDAR-antibody encephalitis in adults: a systematic review and phenotypic analysis of individual patient data

Abstract: Summary Background Early immunotherapy administration improves outcomes in patients with N-methyl-D-aspartate receptor (NMDAR)-antibody encephalitis. As most patients with NMDAR-antibody encephalitis present to psychiatrists, the psychopathology of NMDAR-antibody encephalitis needs to be clearly defined to encourage accurate clinical identification and prompt treatment. Methods For this systematic review, we searched PubMed for all studies published in Engl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
182
0
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(196 citation statements)
references
References 28 publications
4
182
0
10
Order By: Relevance
“…These drugs have also been shown to exacerbate a similarly wide spectrum of symptoms in individuals with schizophrenia, in contrast to amphetamines, which predominantly worsen positive symptoms. Furthermore, it has been shown that anti‐NMDA receptor encephalitis may be associated with psychiatric presentations that resemble schizophrenia in some individuals. NMDA antagonism has, therefore, been proposed to be a superior pharmacological model of schizophrenia, compared to amphetamines, given its ability to more reliably induce negative as well as positive symptoms.…”
Section: Glutamatementioning
confidence: 99%
“…These drugs have also been shown to exacerbate a similarly wide spectrum of symptoms in individuals with schizophrenia, in contrast to amphetamines, which predominantly worsen positive symptoms. Furthermore, it has been shown that anti‐NMDA receptor encephalitis may be associated with psychiatric presentations that resemble schizophrenia in some individuals. NMDA antagonism has, therefore, been proposed to be a superior pharmacological model of schizophrenia, compared to amphetamines, given its ability to more reliably induce negative as well as positive symptoms.…”
Section: Glutamatementioning
confidence: 99%
“…• • NMDAR, VGKR other receptor autoantibodies (the prevalence of these antibodies is potentially of the order of 1-5% but the actual prevalence of the antibodies or the disorders, and the effect of treatment, are not yet clear: Al-Diwani et al, 2019;Pollack et al, 2014;Rickards et al, 2014). • • Consider lumbar puncture (e.g.…”
Section: Diagnosis and Assessmentmentioning
confidence: 99%
“…For example, in NMDAR antibody encephalitis, central psychopathologic features of mood and psychotic disorders consistently coexist within individual patients, although wellcontrolled prospective studies are needed to further advance this approach. 10 The definition of acceptable treatment delay and "red flag" symptoms also requires further evidence-based clarification. For example, a recent cohort study found that delays to treatment longer than 4 weeks and lack of improvement in that time frame were both independently associated with poor 1-year functional outcome, in addition to intensive care unit admission, abnormal MRI, and CSF white blood cell count >20 cells/μL.…”
Section: Discussionmentioning
confidence: 99%